SAPHO (Synovitis, Acne, Pustulosis, Hyperostosis, Osteitis Synovitis, Acne, Pustulosis, Hyperostosis, Osteitis); A Case of Backache in an Adolescent in Pakistan - Dar, Abdul Rehman Azeem; Maira Aleem; Ali Akhtar; Muhammad Zahid Hussain (Pakistan Armed Forces Medical Journal, 2023)
SAPHO (Synovitis, Acne, Pustulosis, Hyperostosis, Osteitis) syndrome is a group of rare auto-inflammatory disorders with a wide range of dermatological and osteoarticular manifestations. Different nomenclatures, like Chronic Recurrent Multifocal Osteoarthritis (CRMO) and Chronic Non-Bacterial Osteomyelitis (CNO), have been used in the past for the same disease, but SAPHO Syndrome has been the accepted terminology since 1990. An adolescent, 17 years of age, with a six-month history of inflammatory backache and fatigue, reported to a rheumatology clinic. His health assessment questionnaire- disability indexcame out to be two. Acne on physical examination raised inflammatory markers, and characteristic findings of SAPHO syndrome on bone scan suggest the disease. The patient was treated with an excellent response to bisphosphonates. The report highlights the importance of the evaluation of inflammatory backache in adolescents. SAPHO syndrome is an underdiagnosed disease. Therefore, more awareness of this disease among healthcare physicians is required.